Factors Influencing Secondary School Students’ Readiness to Learn in the Age of Artificial Intelligence in Saudi Arabia - Al-Mutairi, Mishari M. Q.; Albahiri, Mohammed H.; Alhaj, Ali A. M. (Journal of Cultural Analysis and Social Change, 2026)
By the time students reach secondary education, artificial intelligence (AI) technologies are changing teaching practices, learning environments, and ways of engaging students through flexible, data-driven, and personalized learning systems. Thus, students’ readiness to learn in AI-supported contexts has emerged as a serious education issue, particularly in the context of secondary school, an acute juncture of cognitive, emotional, and social growth. This study employs a descriptive–analytic empirical design to investigate the impact of social, familial, and personal factors on secondary school students’ readiness for learning in the AI era. Data were collected using a structured questionnaire administered to high school students and the data were analysed by descriptive statistics: frequencies, percentages, means, and standard deviations based on participation in a three-point Likert scale. The results show that students are prepared for AI-enhanced learning to a moderate degree. Peer collaboration was identified as the most important social factor, whereas family-related factors, notably parental views of technology as a distraction and a lack of guidance when learning difficulties occurred, negatively impacted readiness. At a micro level, they reported having difficulty with excessive electronic workloads, time management, sustained attention and self-regulation. Overall, students’ readiness for AI-based learning is determined by a combined and moderate degree of social, familial and personal influences, reinforcing the point that a balanced, holistic approach must incorporate technological innovation with supportive social environments, informed family involvement, and the development of the learners’ self-regulatory skills.